Small firms, human capital, and productivity in Asia - Paul Vandenberg; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2016)
The paper analyzes the link between human capital and firm-level productivity in five Asian countries. It draws on a dataset of over 4,000 enterprises and considers both the prior educational attainment of workers and in-service training programs of enterprises. Differences between small, medium-sized, and large enterprises and between countries are also presented. The key finding is that both preservice education and in-service training are positively correlated with labor productivity. The productivity of small and medium-sized enterprises (SMEs) is enhanced by a higher level of skills and education of the workforce, just as it is with large firms. However, there are country differences. The policy implications are that competitiveness is enhanced both by raising the general level of education in the workforce and by encouraging enterprise-based training programs.
Keywords: J24; D22; D24; 330; SME; human capital; firms; enterprises; services; productivity; skills; education; in-service training; labor; workforce; competitiveness; enterprise-based training; People's Republic of China; Indonesia; Malaysia; Thailand; Viet Nam